Penerapan Model Problem Based Learning Untuk Meningkatan Kinerja dan Prestasi Hasil Belajar Fisika Siswa di SMK - Eko Mulyadi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This Classroom Action Research aims to improve the performance and achievement of Physics learning outcomes of XKR1 students at SMK Negeri 3 Yogyakarta with the application of the Problem Based Learning model in learning Physics of Competence in Heat Temperature and Mechanical Properties of Materials. This research is two cycles, each cycle includes four steps, namely planning, action, observation and reflection. The results showed an increase in cycle performance 1: 22.50%, cycle 2: 38.75%, an increase of 16.25%. Increased Physics learning achievement pre-cycle average of 30.75, cycle 1 averaged 65.08, in cycle 2 the average was 72.50. This study was 2 cycles, because in cycle 2, achievement of student learning outcomes reached an average on average 70, the application of the PBL model needs to be applied because of the increase in performance and achievement of learning outcomes.